Time‐release versus immediate‐release formulations of venlafaxine, paroxetine and bupropion: a comparative study of a nationally representative sample of the US working population. Issue 2 (12th February 2014) - Al‐Ruthia, Yazed; Hong, Song Hee
Abstract Objective The purpose of this study is to compare patient‐reported outcomes (PROs) such as health‐related quality of life, mental disorder and psychological distress among users of time‐release (TR) versus immediate‐release formulations of three commonly prescribed antidepressants in a sample of the US working population. Methods Adjusted multiple linear and logistic regression analyses using data from 2004 to 2010 Medical Expenditures Panel Surveys were conducted. The health‐related quality of life was measured based on the Physical Component Summary (PCS‐12) and the Mental Component Summary (MCS‐12) of the SF‐12v2. The mental disorder and the psychological distress were measured by the Patient Health Questionniare‐2 and the Kessler 6 respectively. Key findings The utilization of TR formulations was not associated with higher scores in the SF12‐v2, (β = −0.546, P = 0.442) and (β = −0.806, P = 0.346) for both PCS‐12 and MCS‐12 respectively. The users of TR formulations did not significantly differ in their likelihood of having a score of ≥3 in the Patient Health Questionniare‐2 (OR = 1.048, P = 0.677). Furthermore, the utilization of TR formulations was not associated with lower scores in the Kessler 6 Scale (β = 0.073, P = 0.846). Conclusions Although controlled clinical trials report favourable tolerability profiles for TR formulations, it still remains unclear whether these formulations lead to better PROs in real‐world patient‐care settings.